Nonstationary two-phase flow through elastic porous medium - Bielski, W.; Telega, J.J.; Wojnar, R. (Archives of Mechanics, 2001)
The aim of this contribution is to derive macroscopic equations governing the dynamic flow of two immiscible viscous fluids through an elastic microperiodic porous medium. To this end homogenization methods were employed. The procedure used can be justified by the method of two-scale convergence. Passage to the stationary case and illustrative example were also provided.